Internal Institutionalization of Golkar Party For the Study of Simultaneous 2020 Pilkada (Elections of Regional Heads) in Bandung District - D S Kartini; R Mulyawan; Rudiana (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The research aims to analyze the internal institutionalization of Golkar in Bandung District by taking a case study of the 2020 Pilkada. The method implemented in this research is a qualitative method classified as descriptive, with data collection techniques using documents. The researcher will review those data and give meaning to them. The result of the research is Golkar, which has controlled Bandung Regency for 20 years, turned out to be defeated in the 2020 Pilkada due to the institutionalization of political parties that could not accommodate the wishes of party seniors. By looking at four political parties’ institutionalizations from Huntington, Golkar is one of the political parties with a high survival level and can survive during regime shifts to other regimes in Bandung District. The political party structure is also complex enough, but the political party’s dependency on the mass organization in its winning electoral strategy is still high. The birth of political party intrafraction led to the defeat of the pair of NiaUsman in the battle for Bandung District Regent seat in 2020. In conclusion, Golkar in Bandung District only leaves two things that still exist in party institutions, which are the party chronology and organizational structure. The impact of the research is no matter how strong the party institutionalization is, if it doesn’t accommodate the wishes of the party’s seniors, the institutionalization will be weak, as well as if the party is very dependent on the organization’s wing